Safety Performance in Construction Micro, Small, and Medium Enterprises in Developing Countries - Ranti Taibat Adebiyi; Babalola, Olubola; Zubair Musa Abiodun; Amuda-Yusuf, Ganiyu; Olarewaju Olorunoje, Lukman; Damola Amuda, Aminat (Journal of Technology Management and Business, 2026)
Construction Micro, Small, and Medium Enterprises (CMSMEs) play a vital role in infrastructure and manpower development in developing countries. However, workers in these enterprises are susceptible to safety risks because most of their tasks are handcrafted with little or no machine involvement. This study, therefore, analysed the key drivers to improve safety performance in Nigerian CMSMEs with a view to promoting a proactive safety culture among construction stakeholders. A quantitative research approach was employed, involving the administration of a structured questionnaire to project managers, engineers, and workers across 106 CMSMEs in Abuja, Nigeria. A total of 318 copies of questionnaires were distributed, with a 65% response rate. Descriptive statistics, mean score ranking, and factor analysis were used to analyse the data. The results of the analyses revealed sixteen critical drivers influencing safety performance. The top three drivers were the availability of personal protective equipment, the provision of first aid, and the availability of safety policies. Factor analysis revealed eight major dimensions—provision of facilities, resources, capacity building, financial commitment, government intervention, inspection and monitoring, workforce, and documentation—accounting for 66.9% of the total variance. The Kendall’s Coefficient of Concordance showed a strong agreement among the groups of respondents regarding the rankings of these drivers (W = 0.6671). The study concluded that improving safety performance in CMSMEs requires a multifaceted approach involving adequate safety resources, continuous training, financial investment, stronger regulatory enforcement, and integration of technology. It recommended targeted policies, stakeholder collaboration, and capacity-building initiatives to promote a proactive safety culture, reduce accidents, and enhance sustainability in the construction sector of developing countries.